1987
DOI: 10.1111/j.1943-278x.1987.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Problem‐Solving Deficits in Self‐Poisoning Patients

Abstract: Self-poisoning patients (n = 40) were compared with psychiatric patients (n = 40) and nonpatient controls (n = 20) on measures of interpersonal problem-solving skills and locus of control in an effort to determine the importance of these cognitive and personality variables in self-poisoning behavior. The psychiatric and self-poisoning groups showed deficits on measures assessing interpersonal problem solving when compared with nonpatient controls. The self-poisoning group performed below the level of the psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
140
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(149 citation statements)
references
References 53 publications
8
140
1
Order By: Relevance
“…Of these studies, 63 were identified as potentially relevant to interventions for suicide-related behaviors. Ten studies met the revised inclusion criteria: seven randomized controlled trials (RCTs) [27][28][29][30][31][32][33] and three non-randomized (quasiexperimental) trials. [34][35][36] One study 34 had a duplicate publication.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these studies, 63 were identified as potentially relevant to interventions for suicide-related behaviors. Ten studies met the revised inclusion criteria: seven randomized controlled trials (RCTs) [27][28][29][30][31][32][33] and three non-randomized (quasiexperimental) trials. [34][35][36] One study 34 had a duplicate publication.…”
Section: Discussionmentioning
confidence: 99%
“…37 Five RCTs' samples extended from adolescence to adulthood. [29][30][31][32][33] One in-progress study was identified as relevant; but no data were available and the study was not included in this review. 38 Two studies were excluded based on year of publication [39][40] and we were unable to retrieve three studies through interlibrary loan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since suicidal individuals are thought to often have difficulty in communicating and negotiating their needs and wishes (McLeavey et al, 1994) and to frequently resort to passive avoidant coping strategies (Adams and Adams, 1991), Brent's treatment model encouraged more assertive and direct methods of communicating, as well as increasing the teenager's ability to conceptualize alternative solutions to problems. Meetings with parents were sometimes held to augment the treatment.…”
Section: Cognitive-behavioral Therapymentioning
confidence: 99%